Teach Yourself Electricity and Electronics - Gibilisco, Stan; Monk, Simon (McGraw-Hill, 2022)
Learn electricity and electronics fundamentals and up-to-date applications?all without taking a formal courseThis fully updated guide offers practical, easy-to-follow instruction on electricity and electronics. Written by a pair of experienced instructors, Teach Yourself Electricity and Electronics, Seventh Edition features plain language explanations and step-by-step lessons that make it easy to understand the material quickly. Throughout, detailed illustrations and practical examples reinforce key concepts. This new edition brings the book up to date with modern electronics and places much more emphasis on the use of Integrated Circuits and practical electronics design. You will also get access to a valuable online exam to test your knowledge and identify areas for further study.This thoroughly revised seventh edition covers:Direct current (DC) circuitsElectrical unitsResistorsCells and batteriesMagnetismAlternating current (AC) circuitsInductors and capacitorsPhaseInductive and capacitive reactanceImpedance and admittanceAC power and resonanceTransformers and impedance matchingSemiconductors, diodes, and transistorsIntegrated Circuits (ICs)Amplifiers and oscillatorsWireless transmitters and receiversDigital circuitsMicrocontrollers, including the ArduinoTransducers and sensorsAcoustics and audioAntennas for RF communications